People, possessions and domestic space in the late medieval escheators' records. Issue 2 (15th March 2019) - Briggs, Chris; Forward, Alice; Jervis, Ben; Tompkins, Matthew
ABSTRACT: The medieval English escheator was a royal official who seized the goods and chattels of felons, fugitives and outlaws for the crown's benefit. This article uses escheators' inquests and accounts to ask what information exists about the location of forfeited possessions at the point of their appraisal by the escheator, and what is revealed about the use of space in the houses and outbuildings of lower status people? We also ask more general questions about contemporary understanding of the relationship between domestic objects and space. We find that there was limited interest in describing possessions according to their position within buildings. Nonetheless, one may use the order of items as they are recorded in the escheators' lists of forfeited goods to explore the issues raised in the article. The records reveal an emphasis on the difference between 'household utensils' and other movables, especially crops and livestock.